Haptoglobin polymorphism affects nitric oxide bioavailability in preeclampsia - Sertório, J T; Lacchini, R; Amaral, L M; Palei, A C T; Cavalli, R C; Sandrim, V C; Duarte, G; Tanus-Santos, J E (Journal of human hypertension, 2013)
Studies showed elevated cell-free hemoglobin (Hb) in preeclampsia (PE), and Hb reacts with nitric oxide (NO), decreasing its bioavailability. Haptoglobin (Hp) is a polymorphic protein (Hp1-1, Hp2-1 and Hp2-2) that binds Hb to form a complex that is removed from circulation, thus preventing Hb-driven oxidative stress and NO scavenging. Hp protein products differ in biochemical and biophysical properties, which reflects on the Hb–Hp complex clearance rate. We hypothesized that Hp phenotypes modulate NO bioavailability by influencing NO consumption in PE. We studied 92 PE subjects and 105 normal pregnant women (NP). Hp genotypes were determined using real-time PCR. To assess NO bioavailability, we measured plasma nitrite using an ozone-based chemiluminescence assay. Plasma Hb and Hp were assessed with commercial immunoassays. A NO consumption assay was used to measure NO consumption. We found no differences in Hp genotype frequencies between PE and NP groups. Hp genotypes had no effects on plasma heme levels, NO consumption and plasma nitrite in NP. However, in PE, Hp2-1 and Hp2-2 were associated with higher plasma heme levels (48 and 55% higher, respectively; P <0.05), increased NO consumption (42 and 44% more, respectively; P <0.05) and lower plasma nitrite (39% less for Hp2-2; P <0.05) compared with Hp1-1. These findings indicate that although Hp genotype does not affect the risk of PE, Hp1-1 genotype may exert a protective role in PE by reducing NO scavenging, whereas Hp2-1 and Hp2-2 further may aggravate PE by reducing NO bioavailability.